2005
DOI: 10.1111/j.1365-2648.2005.03573.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ assessment of pain in surgical patients

Abstract: The findings have implications for the management of postoperative pain by highlighting the need for more accurate pain assessment. Further research is required to elucidate the way in which nurses and patients conceptualize pain and to understand better the process of pain assessment in clinical nursing practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
1
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 31 publications
7
75
1
6
Order By: Relevance
“…Although he/she often daily checks up on the patients with Patient Controlled Analgesia or epidural analgesia, the Acute Pain Nurse is not as close to the patient as the ward and PACU nurses are. Another possible explanation of the observed differences is that the Acute Pain Nurses are typically aware of the results of several former studies which have repeatedly demonstrated underassessment and undertreatment of postoperative pain (Idvall et al, 2005;Sloman et al, 2005;Zalon, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Although he/she often daily checks up on the patients with Patient Controlled Analgesia or epidural analgesia, the Acute Pain Nurse is not as close to the patient as the ward and PACU nurses are. Another possible explanation of the observed differences is that the Acute Pain Nurses are typically aware of the results of several former studies which have repeatedly demonstrated underassessment and undertreatment of postoperative pain (Idvall et al, 2005;Sloman et al, 2005;Zalon, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…This might encourage direct assessment of pain (e) rather than reliance on behavioral indicators (Schafheutle et al, 2001), and regular assessment with appropriate pain rating scales (f). given nurses' tendency to under-assess (Sloman et al, 2005).…”
Section: Do the Methods Used In The Education Interventions Map On Tomentioning
confidence: 99%
“…Many of these responsibilities are covered by guidelines on best practice in assessment and treatment (McCafferty & Pasero, 1999). Assessment is ideally by patient report (McCaffery & Pasero, 1999;Turk & Melzack, 2011), but nurses may fail to assess pain adequately (Sloman, Rosen, Rom & Shir, 2005) and/or may substitute their own estimates of pain (Schafheutle, Cantrill, & Noyce, 2001). Treatment may be undermined by excessive fears of unwanted analgesic effects and by inadequate appreciation of pharmacological and nonpharmacological resources to reduce suffering (Liu, So & Fong, 2008;Sloman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Ağrı yönetimindeki bütüncül yaklaşımın hedefi hastanın ameliyat sonrasındaki rahatsızlığını en aza indirmektir 16 . Sekiz Avrupa ülkesi ve İsrail'de yürütülen bir çalışmaya göre (n=4.576) ameliyattan 24 saat sonra hastaların en şiddetli ağrı puan ortalamalarının 5,16 olduğu 17 ; Sloman ve arkadaşlarının yaptıkları çalışmada 18 cerrahi hastalarının %75'inin şiddetli ve orta düzeyde ağrı hissettikleri, ülkemizde ise Özer ve arkadaşlarının 19 yaptıkları çalışmada hastaların %93,7'sinin şiddetli, %50,2'sinin yanma/sızı şeklinde ağrı yaşadıkları belirlenmiştir. Literatürde ağrının etkin bir şekilde kontrol edilmesine yönelik uygulanan kalite yönetimi sonuçlarına göre hastaların ameliyat sonrası yaşadığı en şiddetli ağrı puanında anlamlı olarak azalma olduğu gösterilmiştir 11 .…”
Section: Tartıșmaunclassified